Pengaruh Media Explosion Box Dalam Peningkatan Minat Belajar Sejarah Siswa Kelas X IIS di SMA Negeri 12 Banda Aceh - Eka Deviana (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2021)
This research is entitled “Application of Explosion Box Media to Increase Interest in Learning History at SMA Negeri 12 Banda Aceh”. The problem in this research is the lack of interest in learning history of students. This study aims to determine the interest in learning history of class X IIS students with explosion box media. The type of research used in this research is descriptive with a qualitative approach. The subjects of this research were students of class X IIS 2, totaling 19 students. Data collection is done by observation and questionnaires. The results of observing activities in the implementation of learning are 82% in the very good category. Student interest in the application of explosion box media 23.4% answered strongly agree, 36.2% of students gave interest in agreeing, 34% answered disagreed and 6.2% answered strongly disagreed with either category. So it can be concluded that in the process of applying explosion box media it can increase students' interest in learning history.